Implementasi Pendidikan Islam Pranatal (Studi Kasus Pada Ibu-Ibu Di Ppmi Assalaam Sukoharjo) - Lutfiah, Nur'aini (2016)
This research aims to: 1) get an overview of knowledge of mothers in Assalaam Islamic Modern Boarding School on prenatal Islamic education (baby in the womb). 2) assess whether prenatal Islamic education has been applied by mothers at Assalaam Islamic Modern Boarding School. 3) explore information on how mothers in Assalaam Islamic Modern Boarding School in implementing the prenatal Islamic education. This research is qualitative research with etnography approach. Data was collected by observation, interview and documentation. Data analysis technique using interactive analysis. Results of this research concluded that: 1) Knowledge of mothers in Assalaam Islamic Modern Boarding School on prenatal Islamic education, include Islamic education is applied mother to child in the womb through dhikr, a touch of affection and communication; education by mother's act, education of personality formation, planting of Islamic education to the unconscious baby, education is influenced by the emotional condition the mother. 2) Application of prenatal Islamic education by mothers in Assalaam Islamic Modern Boarding School, includes preparation of financial problems, collect the Islamic books, Islamic CDs, plan islamic recitation activities, and strive for reconciliation themselves and improve behavior and morals that are less well; prepare a plan for wife's activity. Islamic educational materials associated with prenatal, mentioned morals, dhikr, Islamic songs, Quran, Islamic recitation materials, textbooks, hadiths, and role models of parents. The parties involved in Islamic education prenatal, pregnant women itself, husband and parents. 3) Forms of prenatal adoption of Islamic education by mothers in Assalaam Islamic Modern Boarding School include communication invites the fetus, invites worship, charity, read the Koran, listening to music, watching television hafiz of the Koran, read a story book, read prayers, and give a caress in the belly. Media that are used include HP, guitar, laptop, swimming pool, Mp3, studies, books, television, al-Quran, halaqah, neighborhood health center, gadgets, parent voice, and a voice of baby brother.